Adaptor Reconfiguration Analysis in Web Services Composition - 范大娟 黄志球 肖芳雄 彭焕峰 (东华大学学报（英文版）, 2015)
Most of the existing approaches focus on identifying mismatches and synthesizing adaptors at design-time or recently at run-time. However, few works have been proposed to support adaptor reconfiguration when services in the composition evolve due to changes in business needs. To address the deficiencies, the problem of adaptor reconfiguration is targeted in the context of service composition. Firstly, the formal models for describing services and adaptors are presented. Then, under this formalization,the notion of reconfiguration compliance is proposed to determine the validity of an adaptor instance with respect to its history executions and future executions. Based on the notion,the algorithm for reconfiguration analysis of adaptors is presented and it can be used for determining the migratability of an adaptor instance and the corresponding target state of reconfiguration if migratable.Finally,feasibility of the proposed approach is validated on a realistic case study. The proposed approach improves the flexibility of adaptor-based service composition by equipping adaptors with reconfiguration capabilities.